2010
DOI: 10.35305/s.v0i2.39
|View full text |Cite
|
Sign up to set email alerts
|

Modelos PCA a partir de conjuntos de datos con información faltante. ¿Se afectan sus propiedades?

Abstract: En este trabajo se aborda la problemática de la construcción de modelos PCA (Principal Component Analysis) a partir de conjuntos de datos con información faltante. Se trabaja sobre tres situaciones diferentes con relación a la matriz de datos originales. En cada situación se generaron pérdidas a través de mecanismos aleatorios y no aleatorios, en diferentes porcentajes en una sola variable por vez, seleccionada mediante dos criterios: la que más contribuye y menos contribuye en la formación de la primera compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nevertheless, further studies are needed to compare MFA-NIPALS with RIMFA across datasets with higher dimensions, analyzing the computational performance of both methods by comparing the estimated coordinates of ψ (in presence of NAs) with MFA coordinates (of a complete dataset). It is expected that MFA-NIPALS performs better with datasets with more variables than observations (p > n), where PLS methods have advantages over classic methods [48].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Nevertheless, further studies are needed to compare MFA-NIPALS with RIMFA across datasets with higher dimensions, analyzing the computational performance of both methods by comparing the estimated coordinates of ψ (in presence of NAs) with MFA coordinates (of a complete dataset). It is expected that MFA-NIPALS performs better with datasets with more variables than observations (p > n), where PLS methods have advantages over classic methods [48].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Currently, there are other authors working with missing data using the nonlinear estimation by iterative partial least squares (NIPALS) algorithm in multivariate analysis [1,18,19,22], and others working on the data imputation approach with the expectation maximation (EM) algorithm [3,11,12]. It is not exactly known which approach generates better results; however, works have been found that compare them to principal component analysis (PCA) [24].…”
Section: Introductionmentioning
confidence: 99%